The impact of the duration of an untreated episode on improvement of depression and somatic symptoms - Hung CI (Dove Medical Press, 2015)
Ching-I Hung,1,2 Nan-Wen Yu,1,2 Chia-Yih Liu,1,2 Kuan-Yi Wu,1,2 Ching-Hui Yang3 1Department of Psychiatry, Chang Gung Memorial Hospital, Linkou, Taiwan, 2Chang Gung University College of Medicine, Tao-Yuan, Taiwan; 3Department of Nursing, Chang Gung University of Science and Technology, Tao-Yuan, Taiwan Purpose: The aim of this study was to investigate the impact of the duration of an untreated episode (DUE) on the improvement of depression and somatic symptoms among patients with major depressive disorder (MDD), after the patients had received 4 weeks of pharmacotherapy. Methods: In this open-label study, there were 155 participants with MDD who were treated daily with 75 mg of venlafaxine for 4 weeks. DUE was defined as the interval between the onset of the index major depressive episode and the start of pharmacotherapy. The Depression and Somatic Symptoms Scale (DSSS), composed of the depression subscale (DS) and the somatic subscale (SS), was used. The SS included the pain subscale (PS) and the nonpain somatic subscale (NPSS). Multiple linear regressions were used to test the impacts of DUE on the improvement percentages (IPs) of depression and somatic symptoms. Results: Eighty-five subjects completed the 4-week treatment. The IPs of the DS, SS, and NPSS were significantly negatively correlated with DUE. A shorter DUE was related to higher IPs. DUE was an independent factor, predicting the IPs of the DS, SS, and NPSS. DUE <1 month was the most powerful time-point to predict the IPs of the DS, SS, and NPSS. However, DUE was unable to predict the IP of the PS at all time-points. Conclusion: A shorter DUE might be one of the factors related to greater improvement of depression and somatic symptoms. DUE should be considered as an important factor when investigating the prognosis of depression and somatic symptoms. Keywords: early intervention, somatization, treatment response, prognosis, outcome